PENGARUH ONLINE CUSTOMER REVIEW, ONLINE CUSTOMER RATING DAN CASH ON DELIVERY TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI TIKTOK SHOP - Novianti, Anis; Ekowati, Dhiana; Nawarcono, Winanto; Margiutomo, Sapta Aji (Universitas Nusantara PGRI Kediri, 2023)
The development of technology and the internet which is currently increasingly advance and better, makes digital marketing even faster and better.The purpose of this study was to analyze the effect of online customer reviews, online customers rating and cash on delivery on purchasing decisions at TikTok Shop application.This type of research is quantitative using non-probability sampling techniques with a purposive sampling.The results of the analysis in this study indicate that Online Customer Review partially has no effect on purchasing decisions, partially Online Customer Rating has a significant effect on purchasing decisions. Cash On Delivery partially has a significant effect on purchasing decisions. Simultaneously, Online Customer Review, Online Customer Rating and Cash On Delivery has a significant effect on purchasing decisions at TikTok Shop application.